Examining The Impact Of Transformational And Transactional Leadership Styles On R&D Team Performance In UTeM - Othman, Faridatul Sakinah (2019)
R&D is the fundamental element of innovation which subsequently contribute to the idea of knowledge economy, which is crucial for nations to grow. Leadership has been envisaged as one of the most important predictors of team success and performance including in R&D projects. A leader is the head of the team who plays an important role to influence followers and encourage a collective approaches that strongly influences team performance. Besides leadership styles, knowledge sharing has been considered as another significant factor in driving performance due to the advantage of practicing knowledge sharing among team members tends to generate high performance outcomes, improve productivity and profitability. Despite this, there have been a lack of empirical evidence in understanding the role of leaders, especially on leadership styles and contribution of knowledge sharing in influencing team success and performance. The aim of this study was to examine the impact of leadership styles, specifically on transformational leadership and transactional leadership on the R&D team performance. Subsequently, this study was to examine the mediating role of knowledge sharing on the relationship between transformational and transactional leadership and R&D team performance. A quantitative methodology utilising cross-sectional survey was adopted to carry out the research. Data was collected from 172 researcher leaders from Universiti Teknikal Malaysia Melaka (UTeM) based on the database provided by the university’s Centre of Research and Innovation Management (CRIM). Multifactor Leadership Questionnaire 5X (MLQ 5X)was used to elicit the research leaders’ perception on their leadership styles. Next, knowledge sharing was measured utilising journal from Lee (2001) and Bock et al., (2005). Finally, R&D team performance was assessed based on journal from Brown and Gobeli, (1992), Kim et al. (1999b) and Chiesa et al. (2009). Descriptive analyses undertaken provided the details of the demographic profiles of the research leaders participating in this study. Inferential statistics, involving correlational and regression statistics provided the study an overview and understanding on the dynamics of the relationship between leadership styles, knowledge sharing and R&D team performance. The result of this study revealed that both transformational and transactional leadership style have positive impact on R&D team performance. It was also revealed that knowledge sharing partially mediated both transformational leadership and transactional leadership in influencing the R&D team performance. The result of this study offers an insight to research leaders into the practice of leadership, particularly in selecting suitable and appropriate leadership styles, when leading their R&D team. It also provides important input about how knowledge sharing is crucial to be managed as an important activity when undertaking R&D projects. Tags from this library: No tags from this library for this title.